Land Use and Demographic Changes in Haryana: Examining the Relationship Between Land Use Changes and Demographics in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Land use changes are dynamic in nature and should be checked at standard interims for economical advancement. Land use implies use of land in a specific region. Land use design incorporates sorts of land and how much land is being used under various employments. Land is essential asset of human culture and land use is the surface usage of all created and empty arrives on explicit point at a given existence. It is an orderly course of action of different classes of arrives based on certain comparative attributes chiefly to distinguish and comprehend their central utility, brilliantly and successfully in fulfilling the necessities of human culture.